O ônus da prova na fraude à execução de bem sujeito a registro - Rodrigues, Álvaro José do Amaral Ferraz (2019)
Considering the divergences of jurisprudence and doctrine on the burden of proof in the fraud against creditors in execution actions related to property subject to registration, this dissertation aimed to answer the following question: “who has the burden of proof in the fraud against creditors in execution actions related to property subject to registration”. To answer the question, it was initially investigated the most relevant questions concerning the proof and the burden of proof. Subsequently, we analyzed the basic questions concerning the civil execution and, then, it was explained in more details the fraud against creditors in execution actions (thirteen legal hypotheses were found). In the end, it was concluded that, depending on the particular case (or the legal hypothesis of fraud), sometimes the judge will distribute the burden of proof statically and sometimes the judge will the burden of proof between the creditor, the debtor and the third-party